METHODOLOGY OF TEACHING THE TOPIC "HEAVENLY COORDINATES" (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article provides recommendations on the methodology of teaching the subject of celestial coordinates .